Local diagnostic reference levels in fluoroscopy guided procedures in urology, orthopedy and neurosurgery - Cordeiro, Diogo (2022)
The use of imaging in the operating room, namely through fluoroscopy guided procedures, it's commonly used in several surgical practices. Is known that fluoroscopy is a source of ionizing radiation and therefore there's a need to keep the exposure levels on recommended values, as this type of radiation induces biological damages to cell atoms and therefore, it can cause deterministic and/or stochastic effects.